Waiting for answer This question has not been answered yet. You can hire a professional tutor to get the answer.

# Let Y = {1, 2, 3}. Define f : P(Y ) V , where V is as in 2(b), by f(A) = A {4}. Define g : V P(Y ) by g(B) = B {4}. (a) Prove that for each A P(Y )...

Let Y = {1, 2, 3}. Define f : P(Y ) → V , where V is as in 2(b), by f(A) = A ∪ {4}. Define g : V → P(Y ) by g(B) = B − {4}.

(a) Prove that for each A ∈ P(Y ) that g(f(A)) = A.

(b) Prove that for each B ∈ V that f(g(B)) = B.

I don't understand how to approach this question..specifically what the question means..